Impacto do Capital Psicológico no desempenho dos Vendedores de Televendas em uma Empresa Atacadista Distribuidor - Costa, Susiley Corrêa (2019)
The purpose of this study was to verify if psychological capital can influence the gross performance of telesales vendors belonging to a wholesaler distributor. The final sample consisted of 237 salespeople, the majority of whom were female (82.7%), with a mean age of 30 years (SD = 7.63), with an average working time of 42.5 months (SD = 47.5 months) and the mean time in the function was 46.7 months (SD = 45.5 months). The predominant level of education is the high school (40.5%). The instrument used was the Inventory of Occupational Psychological Capital (ICPT-25), composed of four factors and with Cronbach's Alpha greater than 0.70 for each one. The reliability of the scales for the study sample also showed coefficients higher than 0.70. The data were analyzed through descriptive statistics and the model test using Structural Equation Modeling (SEM). The results indicated that the correlations between psychological capital and gross performance were low and the highest correlations were between optimism and hope and self-efficacy with hope. The SEM showed that the proposed model was not confirmed revealing that psychological capital is not a significant predictor of performance of the vendors that composed this sample. It is recommended that in future surveys gross performance be investigated with independent variables of situational character, such as leadership, for example. The study presented contributions to the academic environment when investigating gross performance as a dependent variable, which is innovative within the OPW. For managers, the paper discusses the factors that can determine performance in order to achieve goals in organizations.